2020
DOI: 10.1007/s40415-020-00659-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of two varieties of watermelon (Citrullus lanatus) to different doses of gamma irradiation

Abstract: Watermelon (Citrullus lanatus) is one of the most popular fruits in Cameroon and the world at large. However, the extreme sensitivity of watermelon to parasites and climatic vagaries makes its cultivation demanding of chemical inputs that can have negative impacts on human health and the environment. In Cameroon, there is a slow improvement of fruit yield in watermelon breeding due to the lack of natural heritable genetic variation, which is a prerequisite for genetic improvement of crops. Such variation can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Different types of mutagenesis were employed to induce mutation and genetic variation in Capparis spinosa, gamma rays are highly energetic electromagnetic ions that are released when an atomic nucleus is excited, Gamma rays, administered at various doses with different doses (0.5,1,1.5 K Gray) changed the cytology, biochemistry, physiology, and morphology of cells and tissues, which had an impact on the growth and development of plants. This effect is attributed producing free radicals in cells, (Ernest et al, 2020;Hanafy, R.S. and Akladious, S.A. 2018;Kusmiyati, F. et al, 2017;Elkhateed, M.A.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of mutagenesis were employed to induce mutation and genetic variation in Capparis spinosa, gamma rays are highly energetic electromagnetic ions that are released when an atomic nucleus is excited, Gamma rays, administered at various doses with different doses (0.5,1,1.5 K Gray) changed the cytology, biochemistry, physiology, and morphology of cells and tissues, which had an impact on the growth and development of plants. This effect is attributed producing free radicals in cells, (Ernest et al, 2020;Hanafy, R.S. and Akladious, S.A. 2018;Kusmiyati, F. et al, 2017;Elkhateed, M.A.…”
Section: Introductionmentioning
confidence: 99%
“…When applied at adequate doses, it can provide stimulating effects on the physiological quality of seeds, disinfection of germination inhibiting agents, inactivation of microorganisms, and increases in plant growth and agricultural production; however, high doses (greater than 300 Gy) may inhibit germination (Miranda et al, 2009;Santos et al, 2010;Yun et al, 2013;Nepal et al, 2014;Franco et al, 2019). Before any selection by induced mutagenesis, a radiosensitivity test is thus recommended for measuring mutagenic effects and determining the optimal radiation dose for mutation induction (Ernest et al, 2020). Abu et al (2020) has indicated that mutagenesis induced by doses of gamma radiation from 50 to 200 Gy can be exploited to create genetic variability and favor morphological and yield characteristics in plants.…”
Section: Introductionmentioning
confidence: 99%